Estimulação psicomotora de crianças e seus reflexos na aprendizagem: percepções e potenciais provenientes da aproximação entre universidade e escola - Marques, Rosana Niederauer (2017)
Considering the benefits that the physiotherapeutic intervention, through psychomotor stimulation, can provide in a short and medium term in the development of children, regarding body control and learning, this thesis has the general goal to investigate in what way the psychomotor stimulation of schoolchildren of 4th and 5th years of elementary school, can contribute to the learning of mathematics in two schools in São João do Polêsine City. It is an action research, qualitative-quantitative approach. The participants of the study were 19 children between 9 and 12 years old, of both sexes, belonging to two schools of the São João do Polêsine City, RS. Also part of the research were the teacher regent of each class and 15 academics of the Physiotherapy course of the Federal University of Santa Maria who, in the second semester of 2016, attended the discipline Physiotherapy in Child Health. The selection of the sample was by criteria of convenience and accessibility of the researcher. In order to collect data with the children, a protocol based on the Psychomotor Battery of Vítor da Fonseca (Bateria Psicomotora de Vítor da Fonseca) (1995) was used, and to quantify the mathematical learning, a list of 25 questions was digitized and used as an electronic resource, elaborated from the Protocol California Standards Test. With the children, teachers and conductors with the academics were collected narratives related to the work developed. In addition to the results presented in the body of work, compose the results of the thesis, three articles, one published and two in the evaluation phase and one manuscript, which was a free theme in congresso. The narratives of the teachers and the academics proved the relevance of the work developed with the children and show the relevance to the physical training of the physiotherapist. It is concluded that psychomotor stimulation, corroborating the findings in the literature, favors the corporal control and consequently the learning, reinforcing the argument of the importance of the collaborative work between the University and the School, between the Health area and the Education area.